Effects of condition-based maintenance on costs caused by unscheduled maintenance of aircraft. Issue 4 (10th October 2016) - Gerdes, Mike; Scholz, Dieter; Galar, Diego
Abstract : Purpose: The purpose of this paper is to analyze the effects of condition-based maintenance based on unscheduled maintenance delays that were caused by ATA chapter 21 (air conditioning). The goal is to show the introduction of condition monitoring in aircraft systems. Design/methodology/approach: The research was done using the Airbus In-Service database to analyze the delay causes, delay length and to check if they are easy to detect via condition monitoring or not. These results were then combined with delay costs. Findings: Analysis shows that about 80 percent of the maintenance actions that cause departure delays can be prevented when additional sensors are introduced. With already existing sensors it is possible to avoid about 20 percent of the delay causing maintenance actions. Research limitations/implications: The research is limited on the data of the Airbus in-service database and on ATA chapter 21 (air conditioning). Practical implications: The research shows that delays can be prevented by using existing sensors in the air conditioning system for condition monitoring. More delays can be prevented by installing new sensors. Originality/value: The research focuses on the effect of the air conditioning system of an aircraft on the delay effects and the impact of condition monitoring on delays.